Imitative Words in Yakut and Khakass Epic Texts: Lexical and Semantic Features - Zhirkova, Eugenia Egorovna (Journal of History Culture and Art Research, 2019)
The article presents a comparative study of the sound and image imitative words incorporated in the Yakut and Khakass languages. The study is based on the analysis of the following epic texts: the Yakut olonkho Kyys Debiliye by N.P. Burnashev and the Khakass alyptyh nymaha Ai-Huuchin by P.V. Kurbizekov. These epic texts were selected specifically due to their similarities in plot composition and Yakut and Khakass languages close genealogical relativeness; both languages almost equally contain an abundance of imitative words. The main objective of the present research is to decipher the lexical and semantic features of imitative words contained in the epic text as well as to define the traditional cultural features and universal features, distinctive for both languages under study. In order to achieve the objective, we have set and fulfilled the following goals: lexical material selection form the epic texts; classification of the imitative words by grouping them into thematic categories and subcategories; distinction of the phonetic and semantic correspondences as well as the singling out of universal tendencies, common for both languages, in terms of their use of imitative words. In order to fulfill the main objective of the research, i.e., to study the two closely-related languages based on the olonkho and alyptyh nymah, the following research methods were applied: the method of lexical and semantic analysis, comparative historical research method; when applied, both of these methods allow defining the general Turkic universals and the specific features of the lexical group in question in the two languages, i.e., Yakut and Khakass. In the course of the study, we discovered that the Yakut language imitative words units prevail in quantity. Moreover, the Khakass imitative words possess universal semantic meanings. The author of the present article points out the similarity in the sound and semantic features of imitative words, thus, confirming that both, the Yakut and Khakass people perceive and produce sounds in a similar manner.